A randomized controlled trial of a web-based personalized feedback intervention targeting frequent indoor tanning bed users: Engagement, acceptability, and preliminary behavioral outcomes. (March 2022) - Stapleton, Jerod L; Ray, Anne E; Glenn, Shannon D; McLouth, Laurie E; Parmar, Veenat; Manne, Sharon L
Frequent indoor tanning bed use is an established public health concern, yet research on tanning cessation interventions for frequent tanners is lacking. We describe the protocol for a brief, web-based tanning behavior change intervention and present evidence that it is acceptable and engaging to frequent indoor tanners. Lower tanning rates were not observed among participants receiving the intervention in a randomized controlled trial but participants' interest in changing tanning increased. This intervention could be a useful approach to increasing frequent tanners' interest in behavior change and openness to engaging within a more intensive, multi-component tanning cessation program. Trial Registration: NCT03448224 Clinical Trials.gov (https://clinicaltrials.gov/ct2/show/NCT03448224?cond=NCT03448224&draw=2&rank=1 )